ANTIMICROBIAL POTENTIAL OF Acanthus ilicifolius MANGROVE LEAF EXTRACT AGAINST PATHOGENIC BACTERIA Escherichia coli - Nurul Fahmi Ibrahim; Rahmawati Nur Annisa; Funty Septiyawati (Universitas Mataram, 2026)
This research was motivated by the need for alternative natural treatments for bacterial infections, particularly Escherichia coli, a pathogen that causes gastrointestinal and urinary tract infections. The mangrove plant Acanthus ilicifolius is known to contain bioactive compounds such as flavonoids, alkaloids, and polyphenols, which have antibacterial potential. Therefore, this study aimed to determine the antimicrobial potential of Acanthus ilicifolius leaf extract against E. coli and to determine the most effective extract concentration in inhibiting its growth. The study was conducted experimentally in a laboratory using the agar diffusion method. Leaf samples were collected from the coast of Wara Selatan District, Takalala Village, Palopo City, then dried, ground, and extracted using a maceration method with 96% ethanol. The resulting extract was tested against E. coli at four concentrations: 15%, 30%, and 60%. Paper disks containing concentrated Acanthus ilicifolius extract were then placed on agar media that had been inoculated with E. coli test bacteria, then incubated for 24 hours at 37°C. After that, observations and measurements of the inhibition zone were carried out with a caliper. The results showed that Acanthus ilicifolius leaf extract had antibacterial activity against E. coli, which was indicated by the formation of an inhibition zone around the paper disk. The average inhibition zone ranged from 10.5 mm to 12.5 mm. A concentration of 30% produced the largest inhibition zone of 12.5 mm, indicating the highest effectiveness, although there was no tendency that higher concentrations produced larger inhibition zones. This indicates that the antibacterial effectiveness of the extract is not linear with increasing concentration.